A constelação sistêmica como meio adequado à resolução de conflitos judicializados: elementos imprescindíveis para a sua efetivação. - Rabelo, Patrícia Freire de Paiva Carvalho (2023)
This thesis aims to research the systemic family constellation institute applied to judicialized issues, with the purpose of seeking essential elements for its effectiveness as supporting tool for the adequate resolution of conflicts in Brazil. The study is justified due to the interest of the Judiciary in the use of the technique, as well as the use of some practices of the system. Currently, the method is being applied in 16 (sixteen) Brazilian states and in the Federal District. The concern is dueto the lack of regulation and standardization of criteria for the practice of constellations or their tools, a fact that weakens the application and makes it more vulnerable to criticism. ln such scenario, the standardization of the guidelines for its application is essential so that those under jurisdiction and those applying the law, such as lawyers and judges, for example, can feel safe regarding the use of the method, while also preventing abuses or its inappropriate use. The consensual means of conflict resolution, among which is found the family constellation, are important in order to achieve not only a legal solution, but also a sociological one, that is, the problem is addressed at its root. This fact reduces relapse to the Judiciary, as well as providing a humanized Justice. lt is a systemic view, which brings a new look to Law and its application. ln this respect, the family constellation technique, as well as mediation and conciliation, are important auxiliary tools for Justice. That said, it is necessary to regulate the family constellation with the establishment of essential elements for its employability and systemic practices, as happened with mediation and conciliation. This is important so that everyone can get to know the method better, to curb abuses, to standardize the criteria for its application and, also, to remove the idea that it is somehow linked to religion. As everything that is new is exposed to criticism, the sarne has happened to constellation as well. The big question is in their fundamentais, which for those who deeply understand the technique, demonstrates a great lack of knowledge. This remains noticeable as could be seen in the public hearing that took place in the Brazilian Federal Senate on April 23ʳᵈ, 2022. ln this bias, the research aims to analyze which would be the essential criteria for the regulation of the family constellation. To this end, the constellation technique and the themes related to it were addressed, approaching existing projects, the criticisms and fundamentais of the method, as well as interviews with Sarni Storch, from the Court of Justice of Bahia, responsible for bringing the technique to the Judiciary, and Wilka Vilela who introduced it in the Court of Justice of Pernambuco. Therefore, the thesis is concluded presenting suggestions for regulation and elaboration of a draft bill, which is attached.